Modeling the Growth Potential of the Kelp Saccharina Latissima in the North Atlantic - Strong-Wright, Jago; Taylor, John R. (Frontiers in Marine Science, 2022)
It has recently been proposed that macroalgae (e.g., kelp) could be grown in the open ocean as a CO2 removal strategy. Most macroalgae naturally grow in shallow coastal waters, and their ability to grow in open ocean conditions is largely untested. Here we quantify macroalgae growth potential in the North Atlantic using an established model of Saccharina latissima forced by an ocean state estimate. In the relatively clear open ocean waters, we find that growth is possible to depths of up to 50 m across most of the region, with the maximum depth-integrated growth potential between 40 and 50°N. The model exhibits a large carbon to nitrogen ratio at the southern end of the growth range. The ratio of kelp carbon to phytoplankton biomass is also relatively high in the southeastern portion of the growth range. Using a sensitivity analysis, we find that the position of the southern limit of the growth range is largely modulated by temperature tolerance on the western side of the basin in the Gulf Stream and low nitrate on the eastern side of the basin. We also find a statistically significant reduction in the kelp growth potential over the period from 2002 to 2019, reflecting the warming of the surface ocean over this period.